The Outcome of Percutaneous Mitral Balloon Commissurotomy (PMBC) in Pregnant Women with Mitral Stenosis: An Evidence Based Study: Luaran Komisurotomi Balon Mitral Perkutan pada Perempuan Hamil - Suskhan Djusad; Surahman Hakim; Raymond Surya; Hansens Yansah; Ali Sungkar (Indonesian Journal of Obstetrics and Gynecology, 2020)
Abstract Objective: To review the outcome of percutaneous mitral balloon commissurotomy (PMBC) both to maternal and neonatal. Methods: The search was conducted on Pubmed®, Cochrane Library®, and Ovid® using MeSH. Critical appraisal determining the validity, importance, and applicability (VIA) was conducted by two independent authors. Results: Several studies showed that performing the PMBC had good outcome for pregnant women functional class based on NYHA. Most of them decreased from NYHA III/IV to I/II. For delivery outcome, all studies concluded that more than 80% pregnant women with mitral stenosis undergoing PMBC delivered at term, and no congenital anomalies found. Conclusion: Percutaneous mitral balloon commissurotomy for pregnant women with severe MS is safe during pregnancy. Keywords: mitral stenosis, outcome, percutaneous mitral balloon commissurotomy, pregnancy, Abstrak Tujuan: Mengulas luaran komisurotomi balon mitral perkutan (KBMP) baik pada maternal maupun neonatus. Metode: Pencarian dilakukan melalui Pubmed®, Cochrane Library®, dan Ovid® menggunakan MeSH. Telaah kristis dilakukan oleh 2 penulis independen berdasarkan validitas, kepentingan, dan aplikabilitas. Hasil: Beberapa studi memperlihatkan KBMP memiliki luaran yang baik di kalangan perempuan hamil berdasarkan kelas fungsional NYHA. Kebanyakan mereka mengalami penurunan NYHA dari III/IV menjadi I/II. Untuk luaran persalinan, seluruh studi menyimpulkan lebih dari 80% perempuan dengan mitral stenosis yang menjalani pembedahan KBMP melahirkan pada usia term dan tidak ditemukan kelainan. Kesimpulan: KBMP aman dilakukan pada perempuan hamil dengan mitral stenosis berat. Kata kunci: kehamilan, komisurotomibalon mitral perkutan, luaran, stenosis mitral